Characterization of nucleolar expression and its correlation with the size of the 45S rDNA arrangements in Zea mays inbred lines and hybrids - Carbajal Gonzales, Yajahaira Nevenka (2021)
Ribosomal DNA (45S rDNA) is one of the most well-characterized tandem arrays, formed by a cluster of 18S-5.8S-26S genes and also ITS (internal transcribed spacer) and ETS (external transcribed spacer). In mitotic chromosomes, it is possible to distinguish secondary constriction as a manifestation of a subset of 45S rDNA motifs with active transcription due to RNA polymerase I persistence. Each active motif encodes an 18S, 5.8S, and 26S rRNA transcript. As a result of the ribosomal gene expression and processing and the association with polypeptides, a nuclear structure called a nucleolus is formed. Consequently, there is a relationship between the 45S rDNA transcription and the organization of the nucleolus. The literature has reported the differential expression of secondary constrictions between homologous chromosomes, observing the heteromorphism in the size and intensity of the 45S rDNA. As a result, it was hypothesized that the heteromorphism/homomorphism of the 45S rDNA could occur to different degrees, affecting the nucleolar morphology. In this study, inbred families of maize (JD 1-3, JD 2-1, JD 4-1, and JD 4-4) and their hybrids were analyzed. Qualitative characterization was performed using Fluorescence In Situ Hybridization (FISH) with 45S rDNA probes and fibrillarin immunodetection to describe the secondary constriction in chromosome 6 and in the nucleus of binucleolar cells during the initial interphase. Measurements were made by image analysis, and the data were analyzed using mixed models and multivariate and univariate statistics. The results did not report homomorphism itself; on the contrary, heteromorphism was observed for both the 45S rDNA and the nucleolus in the inbred lines and hybrids. The heteromorphism cases were quantitatively subdivided into three categories according to the value of the indexes of the variables and the heatmap, as slightly, significantly, and notoriously heteromorphic. FISH analyzes have shown that ribosomal DNA varies independently of the mitotic phase. In addition, inbred lines of the families JD 4-4 (3), JD 2-1 (2), JD 4-1 (1) were the most heteromorphic, while the JD 1-3 inbred lines showed lower values, close to the homomorphism. Five different inbred lines of the JD 4-4 family were discriminated as parents of heteromorphic hybrids based on the marking signals for the rDNA 45S probe. The nucleolus analyzes showed heteromorphism in inbred and hybrid lines, mainly involving lines of the JD family 4-4. No structural difference was observed between inbred lines and hybrids. However, the correlation of the results of the 45S rDNA expression with the nucleolar morphology, it was possible to group all genotypes in clusters, observing a slight variation in the degree of heteromorphism of the 45S rDNA between the clusters. At the same time, the structuring of the nucleolus had a homogeneous behavior between them. The heteromorphism in the 45S rDNA can be explained because the rDNA sites may be subject to a higher rate of unequal recombination, which may cause variation in gene copy number. This results in possible epigenetic inactivation mechanisms that could be involved in the control of the ribosomal gene expression.